Analisis Selisih Biaya Overhead Pabrik Dengan Metode Empat Varians Pada PT Pacific Prestress Indonesia - Hutami Hasnau; Sulistia Suwondo (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This research aims to determine the separation of factory overhead cost and to analyze variances of factory overhead costs to the four methods variances in order to know more clearly the cause of the variances. This research was conducted at PT Pacific Prestress Indonesia. Activities PT Pacific Prestress Indonesia is producing precast concrete, minipile foundation, spun concrete, etc. PT Pacific Prestress Indonesia so far have not done the analysis of the variances factory overhead costs to the four difference methods. In this study the authors collected data by using the method of documentation, and interviews. From the research the company has not yet separated overhead costs into fixed costs and variable costs. Variances in factory overhead costs that occurred in PT Pacific Prestress Indonesia is Rp 1.494.231.349,- which represents the excess of gain (favourable), this variance comes from the variance of volume Rp 199.856.586,- (unfavourable and the variance of control Rp 1.694.087.935,- (favourable).